2008
DOI: 10.1590/s0100-06832008000600026
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição do amônio, nitrato, potássio e fósforo em colunas de latossolos fertirrigadas

Abstract: Figueiredo (6)RESUMO Na fertirrigação, é conveniente aplicar os nutrientes de forma a conseguir sua localização na profundidade mais adequada para absorção por parte das culturas: em maior profundidadepara a cultura perene e, mais superficialmente, nas culturas de ciclo curto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(18 reference statements)
0
4
0
2
Order By: Relevance
“…Intriguingly, in this study, higher P contents were found in soils with long history of cultivation, leading to questions about P mobility in Latosols, known to be low (Nancy and Smyth, 1999;Donagemma et al, 2008). It is a consensus in the scientific community that Latosols are soils in advanced weathering stages and their formation involves both geochemical and biological processes.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Intriguingly, in this study, higher P contents were found in soils with long history of cultivation, leading to questions about P mobility in Latosols, known to be low (Nancy and Smyth, 1999;Donagemma et al, 2008). It is a consensus in the scientific community that Latosols are soils in advanced weathering stages and their formation involves both geochemical and biological processes.…”
Section: Resultsmentioning
confidence: 65%
“…In this way, we minimized the influence of management (phosphate fertilization and liming), since P has low mobility in oxidic soils, such as Latosols (Novais and Smyth, 1999;Donagemma et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Excess water increases phosphorus availability to plants due to the occurrence of iron-reduction sites and the resulting solubilization of P-Fe precipitates MIRANDA; The exchangeable K concentration in the soil increased only at the second sampling in the 0-to 5-cm and 5-to 10-cm layers. The increased K concentration in the 5-to 10-cm layer was related to the increased saturation of Ca 2+ and Mg 2+ ions in the 0-to 5-cm layer, which displaced the K + from the exchange complex of the soil solution and consequently increased the K concentration in the deeper layer (DONAGEMMA et al, 2008). The exchangeable K concentration was within the high range (>2 mmol c dm -3 ) according to Cravo, Viégas and Brasil (2007).…”
Section: Resultsmentioning
confidence: 83%
“…Em aplicações de água insuficientes, os sais podem se concentrar em camadas mais superficiais do solo ocorrendo um menor desenvolvimento do sistema radicular que vem a explorar um menor volume de solo, e consequentemente acarreta uma menor produtividade. Porem quando se aplica lamina excessiva, esses nutrientes ficam disponibilizados em uma camada do solo onde não há presença de raízes, promovendo a lixiviação de nutrientes que podem alcançar lençóis freáticos ocasionando contaminações ambientais (Donagemma et al, 2008). Os autores ainda revelam que são poucos os trabalhos em solos tropicais que mostram a eficiência dos nutrientes na fração lamina aplicada, bem como estratégias de parcelamento da fertirrigação como meio de aumentar a produtividade sem causar carregamento de nutrientes para águas subterrâneas.…”
Section: Introductionunclassified